Unpacking the relationship leader affiliative humor and employee innovative behavior: multilevel roles of role breadth self-efficacy and team trust - Zhang, Zheli; Xu, Zhenting; Yu, Ruixiao (Frontiers in Psychology, 2025)
Employee innovative behavior stands as a pivotal factor influencing the core competitiveness of enterprises. Extant research indicates that leadership style is a crucial factor driving employee innovative behavior. Based on social information processing theory, this study focuses on the multilevel mechanism of leader affiliative humor (LAFH) on employee innovative behavior. Through a multi-source, two-stage questionnaire survey, paired sample data were collected from 79 leaders and 302 employees. The results indicate that LAFH has a significant positive effect on role breadth self-efficacy, team trust, and employee innovative behavior, respectively. Role breadth self-efficacy and team trust play a multilevel mediating role in the relationship between LAFH and employee innovative behavior. Besides, team trust exerts a significant multilevel moderating effect on the relationship between LAFH and role breadth self-efficacy, with a stronger positive relationship when team trust is higher.